Boosting the electrochemical properties of carbon materials as bipolar electrodes by introducing oxygen functional groups. Issue 58 (24th September 2020) - Zhang, Yaxiong; Liu, Ying; Bai, Yunfei; Liu, Yupeng; Xie, Erqing
Abstract : Carbon materials with effective oxygen functional groups as positive and negative electrodes and their special energy storage mechanism. Abstract : Carbon materials are often used as both positive and negative electrodes (bipolar electrode materials) in energy storage devices, which significantly reduces the preparation complexity of the electrode. Herein, oxygen-modified carbon nanotubes mounted on carbon cloth (CCC) present a high areal capacitance as both positive and negative electrodes in a safe neutral electrolyte. The introduction of oxygen functional groups facilitates the formation of many electrochemical active sites and defects conducive to ion diffusion. When carbon materials are utilized as negative electrodes, the charge storage characteristics are mainly dependent on the adsorption and desorption of the ions (corresponding to the electric double layer capacitance). Whereas, when utilized as positive electrodes, the charge storage characteristics come from the intercalation and de-intercalation of the electrolyte ions in the multi-defect carbon material. The maximum areal capacitance measured at the positive electrode and negative electrode was 336 mF cm −2 and 158 mF cm −2, respectively. The measured areal capacitance of the assembled symmetrical supercapacitors was 93.6 mF cm −2, and the areal energy density reached 33 μW h cm −2 at a power density of 793 μW cm −2 . It is believed that the efficient preparation method and electrochemical mechanism elucidated in this work can guide the practical applications of carbon cloth in supercapacitors.